A review of heat and mass transfer mechanisms of dehumidifiers and regenerators for liquid desiccant cooling systems. (20th April 2020) - Ren, Haoshan; Sun, Yongjun; Lin, Wenye; Wang, Shugang; Li, Weihua; Ma, Zhenjun
Abstract : Liquid desiccant cooling (LDC) has attracted increasing attention as an alternative to conventional vapor compression systems, to address the challenges of increasing electricity consumption and carbon emissions, and ozone depletion. The major advantages of LDC systems are that they can be driven by low-grade thermal energy such as solar energy and waste heat and can deal with latent load effectively with relatively low energy consumption. This paper provides an overview of the mechanisms governing heat and mass transfer (HMT) of direct-contact and indirect-contact dehumidifiers and regenerators (DRs) used in LDC systems. The results from this review showed that the HMT mechanism of direct-contact DRs using packing materials and fins with complex structures has not been extensively investigated and still remains a research gap to be filled. More in-depth investigations based on meso-scale and micro-scale are needed to investigate the HMT process through the membranes of indirect-contact DRs. The findings discovered can be used to guide future research in the development and optimization of LDC systems.